Relationships between glucose-6-phosphate dehydrogenase, glutathione peroxidase, reduced nicotinamide adenine dinucleotide phosphate, total protein, malondialdehyde, total glutathione and vitamin C parameters in goat milk cells - Kazak, Filiz; Karafakıoglu, Yasemin; Başpınar, Nuri; Peker Akalın, Pınar (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, to reveal the antioxidant potential of goat milk cells, the activities of glucose-6-phosphate dehydrogenase (G6PD), glutathione peroxidase (GPx) and the levels of reduced nicotinamide adenine dinucleotide phosphate (NADPH), total glutathione (tGSH),malondialdehyde (MDA), vitamin C (Vit C) and total protein (TP) in goat milk cells were determined and correlations between these parameters were evaluated. Milk samples were collected from 19 clinically healthy goats from a private goat farm. Briefly, milk cells were collected from milk by centrifugation and than they were sonicated. Supernatant G6PD, GPx activities and NADPH, tGSH, MDA, Vit C and total protein levels were determined by spectrophotometric methods. As regards correlations: milk cell MDA levels were positively correlated with milk cell Vit C (r=0.488, P<0.05) and milk cell NADPH (r=0.589, P<0.05) levels. Milk cell TP levels were positively correlated with milk cell GPx activity (r=0.689,P<0.01). There was positive correlation between milk cell GPx activity and milk cell NADPH levels (r=0.497, P<0.05). Milk cell tGSH levels were positively correlated with milk cell Vit C (r=0.574, P<0.05) and milk cell NADPH (r=0.848, P<0.01) levels. Milk cell NADPH was positively correlated with milk cell G6PD activity (r=0.474, P<0.05). As a conclusion, antioxidant potential of goat milk cells were evaluated and discusses. Key Words: Goat milk cell, GPx, G6PD, NADPH, tGSH